Psychometric evaluation and design of patient-centered communication measures for cancer care settings. Issue 7 (July 2017) - Reeve, Bryce B.; Thissen, David M.; Bann, Carla M.; Mack, Nicole; Treiman, Katherine; Sanoff, Hanna K.; Roach, Nancy; Magnus, Brooke E.; He, Jason; Wagner, Laura K.; Moultrie, Rebecca; Jackson, Kathryn D.; et al.
Highlights: Patient-provider communication is a key element of patient-centered care. Comprehensive, theory-based measure of patient-centered communication (PCC) is needed. The PCC-Ca-36 and PCC-Ca-6 are valid and reliable for colorectal cancer. The measures will aid quality improvement, intervention research, and surveillance. Abstract: Objective: To evaluate the psychometric properties of questions that assess patient perceptions of patient-provider communication and design measures of patient-centered communication (PCC). Methods: Participants (adults with colon or rectal cancer living in North Carolina) completed a survey at 2 to 3 months post-diagnosis. The survey included 87 questions in six PCC Functions: Exchanging Information, Fostering Health Relationships, Making Decisions, Responding to Emotions, Enabling Patient Self-Management, and Managing Uncertainty. For each Function we conducted factor analyses, item response theory modeling, and tests for differential item functioning, and assessed reliability and construct validity. Results: Participants included 501 respondents; 46% had a high school education or less. Reliability within each Function ranged from 0.90 to 0.96. The PCC-Ca-36 (36-question survey; reliability=0.94) and PCC-Ca-6 (6-question survey; reliability=0.92) measures differentiated between individuals with poor and good health (i.e., known-groups validity) and were highly correlated with the HINTS communication scale (i.e., convergent validity). Conclusion: This study provides theory-grounded PCC measures found to be reliable and valid in colorectal cancer patients in North Carolina. Future work should evaluate measure validity over time and in other cancer populations. Practice implications: The PCC-Ca-36 and PCC-Ca-6 measures may be used for surveillance, intervention research, and quality improvement initiatives.